2017
DOI: 10.1016/j.enpol.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the climate debate

Abstract: First-best climate policy is a uniform carbon tax which gradually rises over time. Civil servants have complicated climate policy to expand bureaucracies, politicians to create rents. Environmentalists have exaggerated climate change to gain influence, other activists have joined the climate bandwagon. Opponents to climate policy have attacked the weaknesses in climate research. The climate debate is convoluted and polarized as a result, and climate policy complex. Climate policy should become easier and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 124 publications
0
23
0
1
Order By: Relevance
“…For countries that are yet to introduce a carbon price, one option is to start with a low price and to increase it over time (Tol 2017). Prior economic pricing reforms -such as Stockholm's road pricing scheme (Gu et al 2018) -have become more popular once their effectiveness has been demonstrated.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…For countries that are yet to introduce a carbon price, one option is to start with a low price and to increase it over time (Tol 2017). Prior economic pricing reforms -such as Stockholm's road pricing scheme (Gu et al 2018) -have become more popular once their effectiveness has been demonstrated.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Debates regarding the impact of climate change on societies have persisted due to asymmetries in the capacities of organizations, e.g., expertise, funding, technologies, and data generation, which has been to the detriment of reaching a genuine “global consensus” about greenhouse gas emissions and the state of climate realities (Tol, ). Arguably, the politics behind the determination of reliable and authoritative knowledge necessitates for a global knowledge management process.…”
Section: Global Institutions and The Energy‐environment‐climate Nexusmentioning
confidence: 99%
“…Highly polarized societies are unlikely to come to terms productively with issues that require relatively urgent action, such as most current challenges related to sustainability. Climate change may be argued as a field that has seen growing polarization in the public and political debate leading to ever more extreme positions, heated fights, and relative overrepresentation of rather small but outspoken minorities (Tol 2017). Analyzing ancient Pacific cultures that have reacted differently to sustainability crises (Easter Island and Tikopia), Gowdy (2006) argues that group polarization might have played a significant role in the Easter Island's downfall, because group polarization between competing clans over time perpetuated excessive resource depletion.…”
Section: Group Polarizationmentioning
confidence: 99%